Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.acvd.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Performance of new automated transthoracic three-dimensional echocardiographic software for left ventricular volumes and function assessment in routine clinical practice: Comparison with 3 Tesla cardiac magnetic resonance

Abstract: 3D TTE using new-generation fully automated software is a feasible, fast, reproducible and accurate imaging modality for LV volumetric quantification in routine practice. Optimization of border detection settings may increase agreement with CMR for EDV assessment in dilated ventricles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
6
27
1
Order By: Relevance
“…In the remaining patients, 3D quantification was either unreliable because of insufficient image quality or unavailable because of failure of automated software analysis. Another study recently reported similar findings as 14% of the patients were excluded because of insufficient echogenicity . In patients with atrial fibrillation, recent data suggest that 3DTTE automated software may also provide reliable averaged values of LV variables during multiple consecutive beats …”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In the remaining patients, 3D quantification was either unreliable because of insufficient image quality or unavailable because of failure of automated software analysis. Another study recently reported similar findings as 14% of the patients were excluded because of insufficient echogenicity . In patients with atrial fibrillation, recent data suggest that 3DTTE automated software may also provide reliable averaged values of LV variables during multiple consecutive beats …”
Section: Discussionsupporting
confidence: 57%
“…The software used in our study may overcome such drawbacks, as it offers the possibility to define larger default border detection settings, within the myocardium. Previous study showed that automated border detection standard settings correlate well with CMR in the general population. Nevertheless, more accurate assessment of LV volumes seems to require larger 3D border settings in patients with a dilated LV and altered LVEF …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A previous version of this algorithm was validated for the assessment of LV size and function [19][20][21][22][23] in patients with good quality images, and most recently in unselected patients. A previous version of this algorithm was validated for the assessment of LV size and function [19][20][21][22][23] in patients with good quality images, and most recently in unselected patients.…”
Section: Introductionmentioning
confidence: 99%